Immunomodulation and Regeneration Properties of Dental Pulp Stem Cells: A Potential Therapy to Treat Coronavirus Disease 2019. (19th August 2020) - Zayed, Mohammed; Iohara, Koichiro
The coronavirus disease 2019 (COVID-19) pandemic, originating from Wuhan, China, is known to cause severe acute respiratory symptoms. The occurrence of a cytokine storm in the lungs is a critical step in the disease pathogenesis, as it causes pathological lesions, pulmonary edema, and acute respiratory distress syndrome, potentially resulting in death. Currently, there is no effective treatment that targets the cytokine storm and helps regenerate the damaged tissue. Mesenchymal stem cells (MSCs) are known to act as anti-inflammatory/immunomodulatory candidates and activate endogenous regeneration. As a result, MSC therapy is a potential treatment approach for COVID-19. Intravenous injection of clinical-grade MSCs into COVID-19 patients can induce an immunomodulatory response along with improved lung function. Dental pulp stem cells (DPSCs) are considered a potential source of MSCs for immunomodulation, tissue regeneration, and clinical application. Although some current clinical trials have treated COVID-19 patients with DPSCs, this therapy has not been approved. Here, we review the potential use of DPSCs and their significance in the development of a therapy for COVID-19.